2003
DOI: 10.1073/pnas.0436576100
|View full text |Cite
|
Sign up to set email alerts
|

Interdomain zinc site on human albumin

Abstract: Albumin is the major transport protein in blood for Zn 2؉ , a metal ion required for physiological processes and recruited by various drugs and toxins. However, the Zn 2؉ -binding site(s) on albumin is ill-defined. We have analyzed the 18 x-ray crystal structures of human albumin in the PDB and identified a potential five-coordinate Zn site at the interface of domains I and II consisting of N ligands from His-67 and His-247 and O ligands from Asn-99, Asp-249, and H 2O, which are the same amino acid ligands as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
184
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(196 citation statements)
references
References 41 publications
(42 reference statements)
8
184
0
4
Order By: Relevance
“…Regarding copper ions, serum albumin has one strong binding site in the N-terminal tripeptide (Asp-Ala-His) for Cu(II), but histidine residues are also suggested as a major ligand, similarly to cysteine [35]. Moreover a previous study showed that both metals could be bound to albumin via histidine-imidazole ring in the MBS/site A [17,60], or in N-terminal site for copper [65]. Indeed, both nitrogen atoms of the 17 histidine residues present in bovine albumin are potential donors for transition metal ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding copper ions, serum albumin has one strong binding site in the N-terminal tripeptide (Asp-Ala-His) for Cu(II), but histidine residues are also suggested as a major ligand, similarly to cysteine [35]. Moreover a previous study showed that both metals could be bound to albumin via histidine-imidazole ring in the MBS/site A [17,60], or in N-terminal site for copper [65]. Indeed, both nitrogen atoms of the 17 histidine residues present in bovine albumin are potential donors for transition metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…Another metal binding site, called B, whose location remains unknown was characterized for some metals including Zn(II) [59]. In the metal-binding site A, the imidazole nitrogens of His-67 in domain I and His-247 in domain II could be identified as main ligands for Zn(II) [60]. If site A is the preferential site for Zn(II), it is also a secondary binding site for Cu(II) [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of 111 Cd NMR studies, sitedirected mutagenesis, and molecular modeling, we have proposed that the major zinc site on albumin, termed site A, is located at the interface of domains I and II and is formed by the side chains of His 67 and Asn 99 from domain I and by His 247 and Asp 249 from domain II (Fig. 1B) (17,18). Here, we report the first direct structural characterization of a zinc site on albumin, using Zn K-edge x-ray absorption fine structure (EXAFS) 2 spectroscopy.…”
mentioning
confidence: 99%
“…Model Building and Refinement-The EXAFS data were processed and analyzed as described previously (19) using full (three-dimensional) multiple scattering. We used our model of the zinc site (17), based on a published crystal structure at 2.5 Å of ligand-free (apo)albumin (Protein Data Bank code 1AO6 (9)), as a starting point for EXAFS data refinement. The model included the side chains of His 67 , Asn 99 , and Asp 249 , as well as the side chain and backbone of His 247 and all atoms of Gly 248 , including the peptide bond to Asp 249 (30 atoms).…”
mentioning
confidence: 99%
See 1 more Smart Citation